The Differences in HbA1c Levels in EDTA Blood Samples and Garlic Filtrate Blood Samples - Arista Kurniasari Budi Fristiani; Azana Lathifa Ramadhani; Andri Sukeksi (Universitas Al-Irsyad Cilacap, 2026)
Hemoglobin A1c (HbA1c) is an important parameter used to evaluate long-term glycemic control in patients with diabetes mellitus. The standard sample for HbA1c examination is whole blood with EDTA anticoagulant. However, limitations in the laboratory encourage the exploration of natural alternatives such as garlic (Allium sativum), which contains bioactive compounds with anticoagulant properties. This study aims to determine the difference in HbA1c levels between EDTA blood samples and blood samples treated with garlic filtrate. This experimental study involved 16 samples. Blood was divided into two groups: EDTA and garlic filtrate (40 µL/mL). HbA1c levels were measured using an Alere Afinion analyzer with the boronate affinity chromatography method. Data were analyzed using the Shapiro-Wilk normality test and the Paired Samples T-test. The results showed that the average HbA1c level in EDTA samples was 5.18%, while in garlic filtrate samples it was 5.74%. Statistical analysis showed a significant difference (p = 0.000 < 0.05). This indicates that although garlic filtrate has anticoagulant potential, it does affect HbA1c measurement results.